Tinjauan Yuridis Tindak Pidana Pemalsuan Dokumen Pernikahaan Terhadap Anggota TNI Berdasarkan Undang-Undang Nomor 25 Tahun 2014 (Studi Kasus Putusan No: 44-K/PM.I-02/AD/IV/2018 Pengadilan Militer I-02 Medan) - Agung Poso Siregar; Ridho Mubarak; Alvin Hamzah (JUNCTO: Jurnal Ilmiah Hukum, 2019)
Legal arrangements regarding falsification in the Military Disciplinary Law and knowing the application of criminal law in military justice in the falsification of marriage data documents in decision No. 44-K / PM.I-02 / AD / IV / 2018. This type of research is used normative juridical. Retrieval of data in this study is by taking a copy of the decision regarding the problem of falsification of data falsification documents carried out by individual TNI. The application of criminal law against the perpetrators of falsified criminal acts in the examination of the decision Number: 44-K / PM.I-02 / AD / IV / 2018, the defendant was charged using the indictment of Article 263 paragraph (2) of the Criminal Code and Article 279 paragraph (1) to -1 Criminal Code. Furthermore, the judges' legal considerations in imposing criminal sanctions on the defendant in the decision Number 44-K / PM.I-02 / AD / IV / 2018 the defendant was convicted with a basic prison sentence of 10 (ten) months and charged to pay the cost of a trial case because it was legally proven and convincing falsification.